Strategies for recruitment of adolescent girls into physical activity programmes: a systematic review protocol [version 1; peer review: 2 approved] - Tanya O'Brien; Emer M Barrett; Catherine D Darker; David Mockler (HRB Open Research)
Background Physical activity is essential for youth physical and mental health, yet just 15% of adolescent girls versus 22% of adolescent boys worldwide meet the World Health Organization guideline of 60 minutes of moderate-to-vigorous physical activity per day. As activity patterns established in adolescence often persist into adulthood, there is a looming risk of adverse health outcomes due to insufficient physical activity. A persistent challenge faced by physical activity providers, however, is recruiting adolescent girls into their programmes. This systematic review will quantitatively synthesise existing knowledge surrounding the recruitment of adolescent girls into physical activity interventions and aims to provide evidence-based recommendations for optimal recruitment practices. Methods Five electronic databases will be searched to identify randomised controlled trials of physical activity interventions for adolescent girls worldwide. Hand-searches of reference lists of included randomised controlled trials, relevant systematic reviews, and author publications will also be conducted. Data will be extracted regarding study, participant, and intervention characteristics, pre-determined recruitment goals, recruitment strategies employed, and the number of participants screened, eligible, approached, randomised, and retained. Outcomes will include whether pre-determined recruitment goals were met, recruitment rate, and any adapted or extended recruitment measures required mid-study. Descriptive statistics, including the median recruitment rate for all included studies, will be calculated and stratified by subgroups such as the type or setting of physical activity. Recruitment strategies will be categorised, and the percentage of studies using each category, along with their associated recruitment rates, will be documented. If sufficient studies are found, multi-variable regression will be employed to determine if the use of a specific recruitment strategy increases enrolment. Discussion Application of the findings of this review by physical activity programme providers may enhance their recruitment processes, potentially increasing teenage girls’ physical activity enrolment worldwide. Systematic review registration PROSPERO CRD#42023475858